BRAND IMAGE MODERATION ON IMPULSIVE BUYING BEHAVIOR: EXPLORING THE ROLE OF SOCIAL MEDIA ADVERTISING AND PRODUCT BUNDLING IN COFFEE SHOP - Nindya Saraswati; Yeyen Pratika (Jurnal Manajemen dan Bisnis Performa, 2024)
Nowadays, social media advertising has emerged as a critical marketing tool for businesses. Concurrently, there is a research gap in comprehending the role of social media advertising and product bundling on impulsive buying behaviour and how brand image moderates the relationship. The objectives of this research are to provide a comprehensive knowledge of the dynamics among social media advertising, product bundling, brand image, and impulsive buying behavior, contributing to both academic research and practical marketing strategies. This study is based on a comprehensive survey of Janji Jiwa consumers. The author used a non-probability sampling and distributed questionnaires, obtained 215 respondents. By employing statistical analysis techniques, the findings of this study demonstrates that social media advertising and product bundling significantly affect impulsive buying behaviour. Moreover, this study unveils the moderating role of brand image that enhance the relationships.